The Maltreatment and Adolescent Pathways (MAP) Project: Using Adolescent Child Protective Services Population-Based Research to Identify Research Questions - Wekerle, Christine; Leung, Eman; Wall, Anne-Marie; MacMillan, Harriet; Trocmé, Nico; Boyle, Michael (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2007)
This article introduces readers to the Maltreatment and Adolescent Pathways (MAP) study. The MAP is a longitudinal study that follows active case ﬁles of mid-adolescents in a large urban child protective services (CPS) system. The MAP is a unique opportunity to collect information from teens about their physical health (e.g., sleep quality), mental health (e.g., posttraumatic stress disorder) and cognitive style (e.g., attention, memory). The MAP study samples the population of CPS teens on questions that are used in provincial teen surveys, allowing for points of comparison to non-CPS teens. The MAP tracks youth development over 2.5 years. Although the MAP currently has a very small number of Aboriginal teens, the responses of these teens may focus practitioner and researcher attention to priority areas for further research. This includes the investigation of how some research issues, such as maltreatment history, personal safety, relationship to primary CPS worker and suicidal ideation, may be cross-informative. It is known that teen risk behaviours cluster together, but it is important to understand the relationships among these variables. An understanding of these relationships can drive knowledge creation, as well as practice and policy change. Finally, the MAPstudy has succeeded given a successful collaborative partnership between hospital, university, and CPS partners who both strive to keep the youths’ best interests in the forefront.